Applications of photonic crystal fibers in navigation - Ali Muse, Haider (Technology audit and production reserves, 2015)
Hollow core photonic crystal fibers are inhomogeneous dielectric media with periodic variation of the refractive index. In general, photonic crystals have a photonic band gap. In this paper we proposed to use of a hollow core photonic crystal fiber 1550 nmλ, Ø 10 µm in optical gyroscope. A signal is launched into the fiber in both directions of the loop, i. e., clockwise and counterclockwise, where the optical path length would nominally be the same; however, the Sagnac effect results in a difference in the optical path lengths when the system undergoes rotation. By detecting the two signals on the receive end and combining them, the interference and corresponding phase shift can be related to an angular rotation the interference pattern measured photometrically.